Music and Cross-Curricular Link - Kozole, Nika (Širjenje obzorij o poučevanju glasbe, 2025)
Cross-curricular integration enables different subjects to interact, creating a more meaningful and immersive learning experience for students. Music, due to its universality and its influence on various parts of the brain, plays a vital role in this process. Integrating music with mathematics, foreign languages, sports, art, and social studies fosters the development of diverse skills, including motor skills, linguistic expression, logical thinking, and emotional and social awareness. Additionally, music helps create a relaxed and motivating learning environment, allowing pupils to connect new knowledge with prior understanding more effectively. Strategies such as projects, excursions, and practical workshops serve as essential tools for successful cross-curricular integration. Carefully planned activities enhance the educational process, enabling learners to achieve better results and acquire sustainable and applicable knowledge for the future. This chapter examines methods for integrating music into various school subjects and highlights the benefits of cross-curricular integration for learning and skill development.